Analisis Reaksi Pasar Terhadap Hari Libur Idul Fitri (Holiday Effect) dan Pengaruh Nilai Tukar Rupiah pada Pasar Modal Indonesia - Rohani Risnauli Nababan; Tri Joko Presetyo (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2026)
Each country has different holiday policies, but the number of holidays in Indonesia is quite large, which impacts uncertainty for investors when buying or selling shares. These events can cause market anomalies or irregular market conditions and produce abnormal returns at certain times, known as the holiday effect. This study uses a quantitative descriptive method with an event study approach, data collection is carried out using documentation and literature methods. The data used are secondary data in the form of the Jakarta Composite Index (JCI), the LQ45 Index, and the Jakarta Islamic Index (JII) from the official website of the Indonesia Stock Exchange (IDX). Exchange rate data is taken from the official website of Bank Indonesia. The population of this study is every company listed on the IDX, while the data used are JCI, LQ45, and JII data 6 days before and 6 days after the Eid al-Fitr holiday and regular trading days from 2011-2025. The results of the study show that there is no significant difference in the JCI, LQ45 Index, or JII before and after the Eid al-Fitr holiday, so there is no holiday effect. These results indicate that all three indices reflect a market that tends to be efficient and stable in responding to seasonal events. Furthermore, the Rupiah exchange rate had a negative but significant effect on the Jakarta Composite Index (JCI). The Rupiah exchange rate had a negative but insignificant effect on the JII before and after the Eid al-Fitr holiday. The Rupiah exchange rate had a positive but insignificant effect on the LQ45 Index before and after the Eid al-Fitr holiday.